THE INFLUENCE OF CONSUMER TRUST ON CONSUMER LOYALTY TO CV EXCAVATOR GABRIEL GROUP - Neta Dwi Cahyani,; Rosmayani, (Proceeding International Conference on Social Sciences, 2026)
This study aims to determine and analyze the influence of consumer trust on consumer loyalty at CV Excavator Gabriel Group. The type of research used in this study is descriptive with quantitative methods. The study was conducted at CV Excavator Gabriel Group. Determination of the number of samples using purposive sampling with a total of 38 respondents . The research data source uses primary data collected from questionnaires and content by the research sample. Data analysis in this study uses SPSS assistance. The results of the study indicate that Consumer Trust has a simultaneous effect on Consumer Loyalty. Furthermore, the coefficient of determination (R square) value shows that consumer trust is classified as strong on consumer loyalty at CV Excavator Gabriel Group.